Thermo-Fluid Dynamic Effects of the Radial Location of the Baffle Installed in a Solar Updraft Tower - Saerom Kim; Seungjin Lee; Joong Yull Park (Energies, 2019)
The solar updraft tower (SUT) is a renewable power generation system that uses the natural convection phenomenon of the ground’s air heated by solar radiation. The baffle is a thermo-fluid dynamic structure that improves the heat exchange efficiency and has been recently reported to be a useful tool to increase the output of the SUT. However, one of the less well-known issues is the relationship between the thermo-fluid dynamic characteristics of the flow in the collector of the SUT and the installation location of the baffle and how this affects the power output and SUT efficiency. In this study, the positive and negative thermo-fluid dynamic effects of the baffle, which vary depending on the installation location, are quantitatively analyzed, and the best location is predicted where the overall kinetic power generated by the SUT is maximized. The target SUT model consists of a chimney (12 m height and 0.25 m diameter) and a collector (1 m height and 10 m diameter), and a total of eight model cases are calculated. The results confirm that the kinetic power is lower or higher than that of the control model having no baffle, depending on the baffle installation location. When the position of the baffle is 4.5 m from the center, the increase in kinetic power is maximized by 8.43%. Two important conclusions are that the baffle should interfere minimally with the progress of the main flow into the chimney, generating kinetic power, and at the same time, the baffle should isolate the inner recirculating flow in order to accumulate the heat in the collector so that the natural convection strength is maximized. The perspective gained from the resulting data is useful for SUT design and for pursuing a higher efficiency in the future.